Book review Easy Climatology - Almussa Leite Torres, Guilherme (Geografares, 2021)
This work is a review of the book Climatologia Fácil written by professor Ercília Torres Steinke. The work presents a great contribution to the studies in geographic climatology, mainly because it synthesizes, in a didactic way, the main concepts of climatology in a practical way and how we can recognize them in our daily lives.